MANAGEMENT EFFICIENCY AND FINANCIAL OUTCOMES IN PRIVATE SECTOR BANKS: AN EMPIRICAL STUDY - Anmol Kumari; Anup Kumar Roy (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
In the evolving landscape of India’s banking industry, private sector banks play a significant role in promoting innovation, efficiency, and financial inclusion. Their financial performance is closely tied to how effectively they manage operational resources and human capital. This study aims to analyse the impact of management efficiency on the financial performance of selected private sector banks in India. Specifically, it investigates how efficiency indicators such as cost control and employee productivity influence Return on Assets (ROA), a key measure of profitability. The research covers an eleven-year period from 2013-2014 to 2023-2024, using panel data from five major private sector banks. The analysis employs descriptive statistics, multicollinearity and heteroscedasticity diagnostics, and panel regression through the Pooled Ordinary Least Squares (OLS) technique. Five efficiency indicators - Cost to Income Ratio (CIR), Business per Employee (BPE), Profit per Employee (PPE), Investment to Employment Ratio (IER), and Deposit to Employment Ratio (DER) are used as independent variables, with ROA as the dependent variable. The results indicate that CIR, BPE, PPE, and DER have a statistically significant effect on ROA, while IER does not show a notable impact. The model displays a high level of explanatory power, with an R-squared value of 0.9291, suggesting that approximately 93% of the variation in ROA is accounted for by the selected variables. The findings highlight the importance of operational efficiency and effective human resource management in enhancing profitability. The study offers valuable insights for bank managers and policymakers seeking to optimize performance through strategic efficiency improvements in cost management and employee productivity.